Desempenho agronômico de cultivares de feijoeiro comum (Phaseolus vulgaris L.) em áreas com diferentes potenciais produtivos - Castro, Danimar Manfio de (2018)
The management applied in the areas that have different potentials of grains yields has been one of the alternatives proposed by precision agriculture (PA). The objective of this study was to evaluate the agronomic performance of five common bean cultivars with different growth habits in areas with different grain yield potentials. The study was conducted in 2017 and 2018 harvest in a commercial area in the municipality of Erval Seco – RS, Brazil. Areas of distinct grain yield potentials were defined by overlapping harvest maps. The experiment was allocated in a randomized design area, conducted in a subpartion. The main portions_consisted of three management areas (high, medium and low) and the subportions of five bean cultivars (BRSMG Realce, BRS Radiante, BRS Esteiro, and BRS Esplendor) whit three replicates. The evaluated parameters were: plant stature (EST), insertion height of insertion of the 1st legume (IPLEG), insertion base of the 1st legume (BPLEG), number of total legumes per plant (NLTP), number of legumes per plant on the stem (NLH), number of legumes per plant in the branches (NLR), weight of one hundred grains (PCG) and grains yield (REND). The grain yield showed a correlation with plant stature, height of insertion of the first legume, base of insertion of the first legume, number of legumes per plant in the stem and number of total legumes per plant. It was not possible to verify differentiated performance of bean cultivars tested in the different yield zones (high, medium and low). The average production for the respective 2017 and 2018 harvest were 1,141 kg ha-1 and 2,487 kg ha-1 for the high yield zone, 1,019 kg ha-1 and 2,167 kg ha-1 for the medium yield zone, and 784 kg ha-1 and 1,834 kg ha-1 for the low yield zone. Bean cultivars may present adaptations to the yield potential of grains. In addition, some cultivars may be more stable when directed to the different production environments. The use of bean cultivar positioning by production environment is a new tool and strategy that needs to be further elucidated within the PA. It can contribute in a significant way in maximizing the productive of the crop, in the most varied areas of production in which the bean culture is inserted.